Integrated marketing Communication Strategy for Natural Restaurant and Strawberry Garden - Prabowo, Rendy Satrio; Hudrasyah, Herry (Journal of Business and Management, 2012)
Natural Restaurant and Strawberry Garden is sundanese restaurant with self-picking up strawberry garden that located in tangkubanperahu street no.109,Lembang, West Java. Naturalestablished in September 2008 founded originally as the founder Ir. Dedih Supriyatna.In its development, at the beginning of 2010 Natural decided to shift their business as tourist area, not only restaurant that provide dishes and strawberry chosen as its new concept in order to gain competitive advantages in this competition. Therefore this research is done by competitor analysis and interview to define customer perception toward Natural then determine NaturalÃ¢â‚¬â„¢s new target market Ã‚Â and create integrated marketing communication strategy for their new concept.There are many points resulting from the analysisRumah Strawberry is the competitor for Natural. Rumah Strawberry has advantage in their brand which already been covered by tv program, mainly in culinary tv program. Then, Rumah Strawberry located near some tourist spot like KampungDaun,Kampunggajah,and the Peak this give some advantages and disadvantages because Kampungdaun,KampungGajah,and The Peak give more challenge in attract customer to choose place for eating.Natural has strength in their strawberry product and its strategic location, also has weakness in managerial and marketing activity. Likewise Ã‚Â increase of tourist in Lembang and competitor will be an opportunity and threats of Natural.for their new position as Ã¢â‚¬Å“Sundanese restaurant naunced nature of parahyangan with best quality and quantity strawberry, target market are medium-high and above economic class that looking for experience to picking up strawberry by themselves, from domestic and international originsTo choose which strategies to use, we must see capability and rationale of each strategy. Good marketing strategy and implementation can only be done by a good management. So,it is also important to hire Ã‚Â person who concern in marketing to make their strategies running well.After implementation, Natural need to do evaluation to control the progress and the effectiveness of the strategies. The evaluation recommended every 4 months Ã‚Â refers to Ã¢â‚¬Å“thinkÃ¢â‚¬Â,Ã¢â‚¬ÂfeelÃ¢â‚¬Â,and Ã¢â‚¬Å“doÃ¢â‚¬Â objectives. This short Ã‚Â 4 months period evaluation choose in order to make Natural can take decision rapidly adjust to situation and result of evaluation to make sure the strategies that use implementd goodPurpose:The purpose of this research is to help Natural-restaurant &strawberry garden with propose strategi marketing through Integrated Marketing CommunicationDesign/methodology/approach:The theory used are Zero Based Planning by Tom Duncan to determine IMC, consumer behaviour- AIDA Models to determine objective,andmarketing mix 4P (Product,Price,Place,and Promotion) and below the line Ã‚Â theories to develop the marketing strategy for Natural. The analyses are the current condition and the segmentation analysis of Natural and its competitor, DeÃ¢â‚¬â„¢Ranch and POM TahuLembang, in-depth interview to respondents from travel agent and driver of rental car as stakeholder, and comparison analysis between those three brand.Findings: The end of the research shows that NturalÃ¢â‚¬â„¢s new positioning Ã‚Â delivered through marketing mix (Product,Price,Place,and Promotion) to achieve its objective. For Product, natural need to provide sundanese food and Ã‚Â improvetheir menu with natural speciality dish or signature dish. For price,Natural need to set their price below the competitor to enter the competition easily. For Place, natural need to set their place to be a big tour trip from customer enter until exit from NaturalFor Promotion, Natural should use B2C Ã‚Â Strategy and arrange media communication. B2C strategy with do some cooperation stakeholder like tour&travel agent, driver of rental car, and Bank. the objective of this strategy is to increase amount of Natural visit. Media Communication that choosen are car sticker,brochure, billboard website and social mediaResearch limitations/implications:Research with the scope ofthe city of Bandung and West Bandung regency will be specifically research Natural restaurant and strawberry garden. The strategy will be developed with the focus on Natural overall with the competitor analysis and proposes an integrated marketing strategy through IMC strategies with the goal of increasing the number ofcustomers.In this research not conducted an evaluation of the proposed strategy will be given. This is because it needs to be done to evaluate the implementation of the proposed strategy while researcher faced the limited time in the completion of this study. Therefore, the evaluation can be performed in subsequent studies. In addition, the research will be focused on the proposed strategies needed to develop the Ã‚Â Natural.Practical implications:Theoutcome of this research isintegrated marketing communicationwith Ã‚Â new position as Ã¢â‚¬Å“Sundanese restaurant naunced nature of parahyangan with best quality and quantity strawberrySocial implications:With the conducted integrated marketing communication, Natural could attract more customers and be more competitive in business competition.Originality/value:This research has an outcome which is marketing strategy through integrated marketing communication for restaurant in phase transition of positioning.Keywords: Restauran,Integrated Marketing Communication,Marketing MixCategory:Business Strategy; Marketing.